Interaction between N-fertilizer and water availability on borer-rot complex in sugarcane - Pannuti,Luiz Eduardo da Rocha (2015)
This study aimed to evaluate the effects of nitrogen availability in fertigation and rainfed management, as well as their interactions with the incidence of and damage caused by D. saccharalis and red rot in sugarcane. The experiment consisted of four treatments (0 and 150 kg ha–1 of N-fertilizer with irrigation; 0 and 150 kg ha–1 of N-fertilizer in rainfed management) in a randomized complete block design with four replications. The evaluated parameters were the number of holes and internodes with red rot per meter of cultivation, stalk yield and sugar content. In the laboratory (T = 25 ± 2 °C; R.H. = 70 ± 10%: 12:12-L:D), we evaluated the attractiveness and consumption of fragments of stalks from the different treatments for fourth instar larvae through choice and no-choice tests in a randomized complete block design with ten replications. Nitrogen fertilization via irrigation has favorable effects on borer-rot complex and leads to higher gains in stalk and sugar yields when compared to rainfed management. The increments of stalk and sugar yields due to nitrogen fertilization compensates for the increase in borer-rot complex infestation. In laboratory tests, D. saccharalis larvae were similarly attracted to all treatments regardless of the doses of N-fertilizer or the water regimes evaluated. However, fragments of sugarcane stalks produced with nitrogen fertilization were consumed more by D. saccharalis in both water regimes.